Research-Creations for Speculating About Digitized Automation: Bringing Creative Writing Prompts and Vital Materialism into the Sociology of Futures. (September 2022) - Lupton, Deborah; Watson, Ash
In this article, we present ideas about developing innovative methods for the sociology of futures. Our approach brings together the literature on sociotechnical imaginaries and the sociology of futures with vital materialism theories and research-creation methods. We draw on our research-creation materials from a series of online workshops. The workshops involved the use of creative writing prompts with participants across a diverse range of age groups and locations. The article ends with some reflections on the implications of our approach for researching the futures of emerging digital technologies and the methodological and theoretical development of the sociology of futures.